A comprehensive strategy to clarify the pharmacodynamic constituents and mechanism of Wu-tou decoction based on the constituents migrating to blood and their in vivo process under pathological state. (15th July 2021) - Cheng, Xiaoxu; Lu, Enyu; Fan, Meiling; Pi, Zifeng; Zheng, Zhong; Liu, Shu; Song, Fengrui; Liu, Zhiqiang
Abstract: Ethnopharmacological relevance: As a traditional Chinese medicine (TCM) formula, Wu-tou decoction has been used for treating rheumatoid arthritis (RA) for more than a thousand years. Identifying pharmacodynamic constituents (PCs) of WTD and exploring their in vivo process are very meaningful for promoting the modernization of TCM. However, the pathological state might change this process. Aim of the study: Hence, it is necessary and significant to compare the process in vivo of drugs both in normal and disease state and clarify their action mechanism. Materials and methods: Taking Wu-tou decoction (WTD) as the research object, a comprehensive strategy based on liquid chromatography coupled with mass spectrometry (LC-MS) was developed to identify PCs, clarify and compare their absorption and distribution in normal and model rats, and then explore the potential mechanism of TCM. Firstly, the PCs in WTD were identified. Then, the pharmacokinetics (PK) and tissue distribution of these ingredients were studied. Finally, the constituents with the difference between normal and model rats were selected for target network pharmacological analysis to clarify the mechanism. Results: A total of 27 PCs of WTD were identified. The absorption and distribution of 20 PCs were successfully analyzed. In the disease state, the absorption and distribution of all these components were improved to have better treatment effects. The results of target network pharmacological analysis indicated that PTGS1, PTGS2, ABCB1, SLC6A4, CHRM2, ESR1, ESR2, CDK2, TNF and IL-6 are 10 key targets for WTD against RA. The regulatory effects of WTD on the expression of PTGS2 and TNF were further verified. Pathway enrichment analysis showed that the key mechanism of WTD against RA is to reduce inflammation and regulate the immune response. Conclusion: These results indicated that this strategy could better understand the in vivo process and mechanism of WTD under the pathological state. Furthermore, this strategy is also appropriate for other TCM. Graphical abstract: Image 1 Highlights: The PCs, absorption and distribution of WTD in normal and AIA rats were compared and clarified. In disease state, the absorption and distribution of PCs were improved to have better treatment effects. The main mechanism of WTD in treating RA is to regulate inflammation and immune response.